Contagion of the shareholder market: cases of Colombia, México, Perú, Chile and Argentina (Dimensión Empresarial, 2019)
This document study the existence of financial crisis contagion, it defined like the transmission of the shocks between countries, which translates in increasing in the correlation anything beyond or fundamental link, taking as a source of contagion by EEUU, Brasil, and analyzing Mexico, Colombia, Peru, Chile and Argentina like “Infected” countries, for the period covered between July 3 of 2001, date of unification of the Colombia Stock Market, to July 3 of 2010. To identify crisis period, and to evoid volatility overestimation, it used the algorithm iterative cumulative sum of squares ICCS, developed by Inclan y Tiao (1994), additionally calculated the dynamic conditional correlation (DCC) Engle Model (2002). The document includes a review of several studies, concepts, and transmission (Contagion) methodologies, and it constitutes one of the few studies that includes Colombia like analysis source.  So this study verifies the existence of contagion in the countries studies, except Argentina, but warns that the measure of impact that a crisis in a given country has over other countries is highly sensitive to the way we choose the time window before and after the crisis.
Keywords: Contagion; Crisis; DCC; GARCH; ICSS